Ageing and Water-Based Processing of LiFeMnPO4 Secondary Agglomerates and Its Effects on Electrochemical Characteristics - Benjamin Starke; Stefan Seidlmayer; Oleksandr Dolotko; Ralph Gilles; Karl-Heinz Pettinger (Energies, 2017)
LiFeMnPO4 secondary agglomerates have been aged under different temperature and moisture conditions. The aged and pristine powder samples were then processed to water- and solvent-based cathodes. Structural studies by means of neutron and X-ray diffraction revealed that neither ageing nor water-based processing significantly modified the crystal structure of LiFeMnPO4 secondary agglomerates. Electrochemical characterization was carried out with full-cells. It was found that long-term cycling is similar independent of the solvent used for slurry preparation. Full-cells assembled with water-based cathodes show a better C-rate capability due to a more homogeneous distribution of cathode constituents compared to solvent-based ones. In no case was any negative effect of initial active material ageing on the electrochemical performance found. During ageing and processing, LiFeMnPO4 is effectively protected by carbon coating and water can be completely removed by drying since it is only reversibly bound. This contribution shows that LiFeMnPO4 secondary agglomerates allow simplified active material handling and have a high potential for sustainable water-based electrode manufacturing.